2021
DOI: 10.3390/aerospace8110320
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aircraft Spoiler Demonstrators for Cost-Efficient Investigations of SHM Technologies under Quasi-Realistic Loading Conditions

Abstract: An idealized 1:2 scale demonstrator and a numerical parameter optimization algorithm are proposed to closely reproduce the deformation shape and, thus, spatial strain directions of a real aerodynamically loaded civil aircraft spoiler using only four concentrated loads. Cost-efficient experimental studies on demonstrators of increasing complexity are required to transfer knowledge from coupons to full-scale structures and to build up confidence in novel structural health monitoring (SHM) technologies. Especiall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As shown in previous studies by Winklberger et al, 38,39 the deformation and strains of aircraft spoiler due to aerodynamic forces can be well approximated by an idealized model and a little number of optimized locally introduced forces. It was shown that two symmetrically applied local forces F 1 , F 2 (i.e., four forces) are adequate to imitate the landing load case of a real spoiler (the idealized model/ spoiler is assumed to be symmetrical).…”
Section: Global Modelmentioning
confidence: 72%
See 2 more Smart Citations
“…As shown in previous studies by Winklberger et al, 38,39 the deformation and strains of aircraft spoiler due to aerodynamic forces can be well approximated by an idealized model and a little number of optimized locally introduced forces. It was shown that two symmetrically applied local forces F 1 , F 2 (i.e., four forces) are adequate to imitate the landing load case of a real spoiler (the idealized model/ spoiler is assumed to be symmetrical).…”
Section: Global Modelmentioning
confidence: 72%
“…Thus, the utilized test rig was developed to approximate this important load case with respect to deformation and strain at the pressurized spoiler surface by only four local loads distributed via the whiffle tree. 38,39
Figure 6.Image of the experimental set-up of the idealized spoiler model.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63][64][65] Methods for damage identifications based on strains recorded from zero-strain trajectories are also employed. 35,66,67 Lately, strain-based SHM methodologies utilizing the inverse FE method are emerging. [68][69][70] As previously mentioned, aerospace structures are designed under the principles of damage tolerance, operating under the existence and development of damage, intrinsic or induced, within their volume.…”
Section: Strain-based Shm Methodologiesmentioning
confidence: 99%
“…Recent studies have focused on the development of novel systems for structural health monitoring (SHM), based on the continuous and distributed monitoring of low-impact occurrences, with the aim of achieving early detection of potential structural damage during aircraft operating time [ 5 , 6 , 7 ]. This would prevent the late detection of more serious damage, which requires more expensive repairing interventions when possible, or the use of expensive techniques for non-destructive testing and evaluation (NDT&E) [ 8 , 9 , 10 ]. The use of SHM technologies in the aviation market will have a commercial impact, possibly reducing maintenance costs by up to 40% and also modifying the repairing process, leading to a move from time-based maintenance (TbM) to condition-based maintenance (CbM) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%